Scientific Framework of Nahdlatul Ulama Education and Its Contribution to the Development of National Education - Sembodo Ardi Widodo (Edukasia Islamika, 2021)
The existence of Nahdlatul Ulama (NU) is inseparable from education. The birth of NU itself is also driven by the kyai who are also leaders in Pesantren (Islamic boarding schools). The growth of NU can be said to be in line with the growth and the development of pesantren educational institutions, madrasa educational institutions, and schools under the auspices of the Ma'arif institution. From year to year, the number of pesantren, madrasas, and schools managed by NU and also nahdliyin(communities who affiliate with NU organization) is increasing. This shows that NU, in terms of education, has made many scientific contributions to the Indonesian nation. This article is intended to explain the contribution of NU in education in Indonesia. The study is directed at describing the history of the development of NU as an Islamic religious organization, the scientific and ideological framework that is used as the basis for thinking and behaving, as well as the development of NU educational institutions in the context of realizing the goals of national education.